1997
DOI: 10.1046/j.1537-2995.1997.37497265345.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual transmission of hepatitis C virus to a repeat blood donor

Abstract: Heterosexual transmission of HCV can occur in the absence of a long-lasting contact, and the infection can be asymptomatic. It remains to be determined whether the sexual partners of HCV-infected subjects should be deferred from blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The similarity of the virus in the couple was 93.4% (E2/NS1 region). No other risk factor was identified 7 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The similarity of the virus in the couple was 93.4% (E2/NS1 region). No other risk factor was identified 7 .…”
mentioning
confidence: 97%
“…In a report by CAPELLI et al (1997) 7 a female repeat donor was surprised to learn that she was PCR-HCV positive, sometime between the two donations. She noted that she lived with a sexual partner who was a chronic HCV carrier.…”
mentioning
confidence: 99%
“…1,2 The strength of these reports lay in their ability to document seroconversion in an individual at risk in temporal relationship to sexual activity with an HCV-infected partner. The mode of transmission was ascertained by carefully questioning the infected individual to exclude nonsexual sources of HCV.…”
mentioning
confidence: 99%
“…28 Morsica et al and Capelli et al reported acute infection of only one female patient, with similarities of 94.9% and 93.4%, respectively, with an HCV-positive sexual partner being the only risk factor in the two studies. 7,23 Chayama et al reported similarity ranging from 91.4% to 99.8% in eight cases seen at a hepatology service. 29 Williams and Alter, researchers at the Viral Hepatitis Division of the Centers for Disease Control and Prevention, followed up 263 cases of acute hepatitis C and 13% of these patients reported sexual exposure as the only source of risk for the acquisition of the disease.…”
Section: Virologymentioning
confidence: 98%
“…She admitted a sexual partnership with a man with chronic HCV infection. 23 According to Weisbord et al, having sexual contact with an HCV-positive person was independently associated with being anti-HCV positive. 15 In the case of HCV-positive patients, it is still not possible to clearly distinguish between those who present a potential of sexually transmitting HCV and those who do not.…”
Section: Epidemiologymentioning
confidence: 99%